Beneficial Effect of Antibiotics and Microbial Metabolites on Expanded Vδ2Vγ9 T Cells in Hepatocellular Carcinoma Immunotherapy - Han, Jiajia; Zhang, Siya; Xu, Yi; Pang, Yongsheng; Zhang, Xue; Hu, Yu; Chen, Hui; Chen, Wanjun; Zhang, Jianmin; He, Wei (Frontiers in Immunology, 2020)
Animal experiments and clinical trials have shown that the gut microbiota modulate host immunity and the immune checkpoint-mediated responses to tumor cells. However, it remains unclear whether microbiota can also play a role in tumor immune response of gamma delta T cell, a kind of cells target cancer directly. Here, we are reporting the microbiota dysbiosis induced by antibiotics enhanced gamma delta T cell efficacy during tumor therapy in a mouse model. Further microbiota and metabolite analysis revealed that the alteration of gamma delta T cell cytotoxicity might be closely associated with specific metabolites, which are produced by intestinal bacteria and stimulate gamma delta T cell to release more cytotoxic cytokines, such as granzyme B and perforin. Among the metabolites that we analyzed, 3-Indolepropionic acid (IPA) showed the highest concentration in antibiotic-treated mice and can improve the cytotoxic ability of gamma delta T cells both in vitro and in vivo. Our research determined how the gut microbiota can influence the antitumor ability of gamma delta T cells and identified potential intermediate molecules that connect the gut microbiota and gamma delta T cells.